1994
DOI: 10.1002/neu.480251204
|View full text |Cite
|
Sign up to set email alerts
|

The growth of PC‐12 neurites is biased towards the anode of an applied electrical field

Abstract: We have exposed cultures of PC12 cells to uniform DC electric fields following the addition of NGF. The success of these experiments relied upon the design of new chambers enabling fields to be applied to mammalian cell cultures. After 48 h of field application, the distribution of neurite outgrowths was biased towards the anode. More neurites faced the anode than would be expected if growth was uniform. The magnitude of this bias was strongly correlated with field strength, with a threshold value of about 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 25 publications
(25 reference statements)
4
33
0
Order By: Relevance
“…Similarly, studies in Xenopus have shown that cell surface receptors for neurotransmitters undergo a cathodal reorientation in an electric field (28), although other studies also in Xenopus demonstrate that neurites can turn either toward the cathode or anode depending on the identity of the substratum (29). In contrast, Davenport and McCaig (31) found that dendrites turn cathodally while axons do not respond, whereas Cork et al (30) found that PC-12 cell neurite turn toward the anode. Thus, the true effect of electrical stimulation on neurite outgrowth is still the subject of debate.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, studies in Xenopus have shown that cell surface receptors for neurotransmitters undergo a cathodal reorientation in an electric field (28), although other studies also in Xenopus demonstrate that neurites can turn either toward the cathode or anode depending on the identity of the substratum (29). In contrast, Davenport and McCaig (31) found that dendrites turn cathodally while axons do not respond, whereas Cork et al (30) found that PC-12 cell neurite turn toward the anode. Thus, the true effect of electrical stimulation on neurite outgrowth is still the subject of debate.…”
Section: Discussionmentioning
confidence: 97%
“…In response to EFs, PC12 neurite outgrowth was biased toward the anode. This asymmetry was entirely due to the inhibition of cathodal growth (Cork et al, 1994), mirroring the effect of EFs on chick DRG neurites. No turning or stimulation of growth toward the anode was observed.…”
Section: The Responses Of Cultured Mammalian Neurons To Efsmentioning
confidence: 90%
“…Growth cones change their direction of migration in a DC EF depending on the substratum adhesivity and net charge (167). Sensory neurites do not turn (93), motor neurites turn cathodally (78), and PC12 neurites turn anodally (42). Moreover, embryonic rat hippocampal dendrites were attracted cathodally, but the axon on the same cell body did not turn (46).…”
Section: Embryonic Frog Spinal Neurons As a Model Systemmentioning
confidence: 99%